2015
DOI: 10.1590/1519-6984.08314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the organophosphorus pesticide Folisuper 600 (methyl parathion) on the heart function of bullfrog tadpoles, Lithobates catesbeianus (Shaw, 1802)

Abstract: The aim of this work was to evaluate whether the heart function of bullfrog tadpoles (25 Gosner stage) is affected by their acute exposure (48 h) to a sub-lethal concentration (10 µg.L -1 ) of the active principle of the organophosphorus pesticide Folisuper 600R (methyl parathion -MP). Our results demonstrated that MP causes not only a reduction in tadpoles' cardiac ventricular mass, resulting in a marked reduction in their cardiac twitch force, but also impairs their swimming performance, irrespective of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Therefore, the reduction in the tadpoles' activity level in response to LAS exposure is probably due to the fact that this xenobiotic inhibits acetylcholinesterase's (AChE) activity in the motor end-plate of the skeletal muscle fiber, impairing tadpoles' swimming performance. Similar results have been observed in bullfrog tadpoles in response to the exposure to other lipophilic contaminants, such as methyl parathion (Costa et al, 2015) and endosulfan (Denoël et al, 2013). In addition, studies have demonstrated a decrease in the swimming activity in response to the inhibition of AChE in some fish species (Brewer et al, 2001;Rao et al, 2005;Ballesteros et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, the reduction in the tadpoles' activity level in response to LAS exposure is probably due to the fact that this xenobiotic inhibits acetylcholinesterase's (AChE) activity in the motor end-plate of the skeletal muscle fiber, impairing tadpoles' swimming performance. Similar results have been observed in bullfrog tadpoles in response to the exposure to other lipophilic contaminants, such as methyl parathion (Costa et al, 2015) and endosulfan (Denoël et al, 2013). In addition, studies have demonstrated a decrease in the swimming activity in response to the inhibition of AChE in some fish species (Brewer et al, 2001;Rao et al, 2005;Ballesteros et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Results are presented as Means ± S.E. only been undertaken recently (Costa et al, 2008(Costa et al, , 2015Dal-Medico et al, 2014;Rissoli et al, 2016;Salla et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the effects of cholinergic overstimulation previously described in mammals are tearing, sweating, cardiorespiratory alterations, salivation, changes in the central nervous system, bradycardia, as well as muscle necrosis ( Nunes, Carvalho & Guilhermino, 2005 ). Costa et al (2015) also demonstrated this bradycardia in bullfrog tadpoles exposed to environmental stressors (i.e., exposure to an organophosphate).…”
Section: Discussionmentioning
confidence: 66%
“…This results in a negative chronotropic response, with reduction of the self-depolarization rate of pacemaker cells ( Pelster et al, 1993 ). Therefore, Bd could either stimulate the parasympathetic system, or inhibit the activity of the enzyme acetylcholinesterase (AChE), which is responsible for ACh hydrolysis ( Costa et al, 2015 ). Consequently, ACh accumulates in the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%